From the forest to the table: Hunting and consuming wild boar in Portugal in Early Modern Age (TEL Tempo, Espaço e Linguagem, 2024)
The wild boar (Sus scrofa) is a mammal that has long existed in Portugal. The main sources to study it are those related to its hunting or consumption. Hunting doesn’t always imply consumption, and the opposite is also true. But in Early Modern Age, as today, it was the predominant way of obtaining wild boar for consumption. This article focuses on understanding the methods and processes surrounding the hunting and consumption of this swine in royal and aristocratic contexts. Keywords: Wild Boar. Hunting. Food Consumption. Portugal. Early Modern Age.